Psychometric properties of learning environment diagnostics instrument - Setiawan, Risky; Hadi, Samsul; Aman, Aman (Intelektual Pustaka Media Utama, 2024)
The rise and growing prevalence of juvenile delinquency is a matter of concern for many parties. This study aims to establish a research instrument in the form of a questionnaire that can be deployed to assess the learning environment perceived by high school students. This research endeavor constitutes a developmental study, wherein the outcomes are a single survey instrument encompassing six variables, nineteen indicators, and forty questions. The data-collecting process involved the utilization of a Google Form across five schools in five districts, containing a total of 1615 participants. The analysis of expert data was conducted utilizing V. Aiken and field trials employing confirmatory factor analysis (CFA) Second Order. The findings of this study indicate that the diagnostic survey instrument used to assess the learning environment's impact on the mental health of high school students demonstrated validity, as evidenced by loading factor values exceeding the established minimal threshold. The reliability of the instrument remains insufficient. This survey can be utilized to detect adolescent persistent tendencies carried out by students or other school members that interfere with mental health: the emergence and significant raising of juvenile delinquency.